Evaluation of radiation damage exposure for low alloy steel in J-9 irradiation channel of Argonauta reactor - Jonnathan Ogihara; Pedro Benevides Ribeiro da Silva; Fernando Manuel Araújo Moreira (Brazilian Journal of Radiation Sciences)
The operation of nuclear facilities must satisfy the nuclear safety requirements. An analysis of the components of these facilities focuses on the structural materials. In this scenario, several types of alloys are employed in their construction. The nuclear fuel burn-up will result in damage caused by ionizing radiation. Due to continuous operation, radiation damage will build up and may result in the manifestation of macroscopic radiation effects. Such effects may change the mechanical, physical and chemical properties of structural alloys. Thus, it is verified the importance of the material behavior predictability to avoid reduction in performance or failure in these types of facilities. In order to study these effects, it’s necessary to calculate the displacement per atom (dpa) in the material. This calculation was estimated for the reactor Argonauta’s irradiation channel J-9 for low alloy steel. An ideal situation with a harder neutron spectrum was calculated to analyze the results. The dpa rate calculated in that facility was attributed to the low neutron energy fluence.